The political economy of sustainability - Gale, Fred P.; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
Innovatively rethinking the discipline of political economy, Fred P. Gale builds on a range of contemporary examples to develop a pluralistic conception of sustainability value that underpins sustainable development. He identifies why current approaches are having no meaningful impact and unifies diverse perspectives into one integrative approach. This definitive work argues that sustainability value's realization requires a complete rethink of the way firms and polities are governed, challenging the idea that preferences are rational. Treating sustainability value as supervening on four other elemental economic values, the book illustrates how 'tetravaluation' is being partially realized at the level of the firm and the state. With vast differences in institutional requirements across conventional liberal, nationalist and socialist frameworks, Gale implores political economy to abandon its monistic modernist legacy and embrace the pluralistic, reflexive and interdisciplinary standpoint that sustainability demands. With striking implications for existing political, economic and cultural institutions, Gale offers a new perspective on generating better policy outcomes for public policy professionals and sustainability practitioners. This book is a must-read for public policy theorists, political and ecological economists, and environmental policy researchers, as Gale challenges the conventional ideas linked to the functioning of liberal democracy and explores the future of political economic thought.
Contents: 1. Introduction -- 2. Economic value in political economic thought -- 3. Economic value in environmental thought -- 4. Synthesizing sustainability value in sustainable development -- 5. Measures of sustainability value -- 6. Governing business for sustainability value -- 7. Governing the polity for sustainability value -- 8. Governing preferences for sustainability value -- 9. Conclusion: getting to sustainability value -- References -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: Sustainability -- Political aspects; Electronic books